More Alike, More Forgiving: What Builds Stronger Student Friendships? - Faruq, Dara Asmarani; Agung M. Iqbal; Annisa Fitriani (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study examines the relationship between forgiveness, similarity, and friendship quality among students at the Faculty of Da'wah and Communication Sciences, UIN Raden Intan Lampung. A correlational quantitative method was employed with 65 participants selected via purposive sampling. Three psychological scales were used: Friendship Quality Scale (α=0.836), Forgiveness Scale (α=0.880), and Similarity Scale (α=0.927). Multiple regression analysis revealed significant relationships between variables (R=0.498; p<0.001) with a combined contribution of 24.8%. Partial analysis showed moderate correlation between forgiveness and friendship quality (r=0.321; p=0.009), while similarity demonstrated stronger correlation (r=0.417; p<0.001). Notably, similarity contributed more substantially (16%) than forgiveness (8.7%) to friendship quality, indicating that group homogeneity factors outweigh forgiveness capacity in maintaining peer relationships among university students. Keywords : emerging adulthood, friendship quality, interpersonal relationships, forgiveness